G209 Promoting Multiprofessional Learning Through the Development of a Standardised Paediatric in Situ Simulation Programme; A Multi-Centred Approach. (24th May 2017) - O'Loughlin, K; Dimmock, V; Runnacles, J; Botting, N; Lanlehin, R; Wong, S; Lofton, L
Abstract : Aims: A regional scoping study was set up across our network to assess the delivery of multiprofessional paediatric in situ simulation (MPIS). The aim was to promote the delivery of multiprofesisonal learning through the development and implementation of a standardised MPIS programme based on the ASPiH (2016) Standards for Simulation Based Education in Healthcare. Methods: The scoping study identified 88 simulation leads across 11 hospitals. Semi-structured interviews and a questionnaire study were used to assess MPIS provision based on 7 key areas outlined by the ASPiH (2016) standards. From this scoping study, a needs assessment and development of driver diagrams informed the creation of a MPIS programme. Integral to this programme was the design of simulation scenarios with mapped learning objectives for nurses, level 2 paediatiric trainees (based on RCPCH curriculum) and human factors learning to promote equal learning opportunities.The effectiveness of this programme in promoting multiprofessional learning was evaluated using a 14 item questionnaire comprising 5 point Likert scale to assess participants' perceptions that simulation supported multiprofessional learning pre and post participation in MPIS. Results: Diverse practice was evident in the delivery of MPIS, across our regional network. Prior to MPIS, 53% did not engage in regular delivery of multiprofessional simulation and 71% identified no structured learning objectives for nurses. Subsequently, the MPIS programme was developed and piloted across 8 hospitals. In total 18 MPIS were delivered to 74 participants. Paired T Test statistical analysis demonstrated significant improved perception that simulation supported multiprofessional learning following participation in MPIS (t(73) =8.51, p<0.001) from a mean of 46.8 (SD=7.6) to 54.7 (SD 5.3). A mixed ANOVA subset analysis was performed to assess whether there was a significant difference in increased perception between professional groups (doctors and nurses). ANOVA demonstrated significantly improved perceptions for both groups (F(1, 72) =71.0, p<0.001) with both professional groups' perceptions improving to the same degree (F(1, 72)=0.11, p=0.74). Conclusion: The MPIS programme has a positive impact on perception of multiprofessional learning through simulation. Our programme provides a standardised structure for the regional delivery of MPIS that supports multiprofessional learning that is valued by both doctors and nurses.